Mathematical simulation and research of vapor-liquid equilibrium in systems ethanol/water/ethylenediamine and ethanol/water/butylamine - T. V. Chelyuskina; M. Yu. Marchenkova; A. A. Kulakova (Тонкие химические технологии)
Wilson and NRTL model parameters for binary components of ethanol-water-ethylenediamine and ethanol-water-butylamine systems were estimated. Besides, the mathematical simulation of vapor-liquid equilibrium in binary and ternary systems under atmospheric pressure was realized.